Synthesis of Composite ZnO-Zeolite and Its Application as Adsorbent: A Systematic Review - Veronica, Jessica; Mollah, Mamun; Anwar, Budiman; Yuliani, Galuh (Jurnal Kartika Kimia, 2024)
This article aims to determine the most effective ZnO-zeolite synthesis method for use as an adsorbent. The effectiveness of the ZnO-zeolite synthesis method includes the methods of synthesis, characterization, and adsorption. This study is a literature search using Google Scholar and Science Direct with the keywords “ZnO”, “zeolite”, “synthesis”, and “adsorption” taken from the last 10 years (2013-2023). Twenty-six articles were obtained, and selection was carried out so that 12 articles were obtained. There were 4 methods for ZnO-zeolite synthesis: (1) sol-gel, (2) impregnation, (3) coprecipitation, and (4) hydrothermal methods. The synthesis of ZnO-zeolite products was characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM), and their adsorption capacity was tested via UV-Vis spectroscopy. The hydrothermal synthesis method is the most effective method for the synthesis of ZnO-zeolite because it does not consume a large amount of energy, is a simple synthesis procedure, and has a large adsorption power. The resulting ZnO-zeolite has a crystal size of 1.540 mm and can adsorb up to 657.895 mg/g of the adsorbate).